Pelatihan Aksesibilitas Media Pembelajaran Berbasis Teknologi Virtual Reality Bagi Siswa Berkebutuhan Khusus - Anita; Subari; Nira Radita (Jurnal Pemberdayaan Masyarakat, 2025)
Early childhood education is currently facing challenges in ensuring that children with special needs also get the same opportunities to learn and develop, this is also a challenge for KB-RA Terapi Tazkiyah Malang. The existence of inclusion classes creates its own problems for schools, namely the limited understanding of teachers on teaching methods for inclusion students, limited teacher skills in preparing learning media that are suitable for all students and limited variations in learning media used. Through community service activities, training is conducted for teachers to improve skills in managing inclusive classes, introduce virtual reality (VR) technology as one of the learning media for students and assist teachers in preparing VR-based learning media. VR creates a three-dimensional digital environment that allows students to interact with objects or situations as if they were real, even though they are in cyberspace and provide immersive experiences that make students feel they are in a certain place or situation so that students will learn in a fun and directed atmosphere. The results of the training show an increase in the level of empowerment of partners in increasing the accessibility of learning media by applying VR technology, increasing insight into the diversity of learning media and skills in preparing appropriate, varied and innovative learning media.